Gymnastic skills and body positions in function of the correct posture in preschool and early school age children - Spasovska, Katerina; Aceski, Aleksandar; Vuksanovikj, Vladimir (Faculty of physical education sport and health, 2019)
Everyday fulfilled with sitting in front of a computer and physical inactivity are equivalent to bodily deformities and poor body posture. Gymnastics is a sport that offers good stability and control of various movements that are very important for the development of children. With its many movements, positions and elements, gymnastics is an indispensable means of physical exercise that affects all body segments and thus affects the proper development of the whole body as well as the proper posture. A wealth of movements that abound in sports gymnastics, the various positions allow one who practices them to build a vast fund of motor knowledge. Therefore, gymnastics should take a special place in physical education from an early age, as its daily practice affects the formation of a fit body, restoring the body to its original state, but also to prevent various deformities.
Keywords: sports gymnastics; preschool; early school age